Interrelation between the distributions of kinetic energy release and emitted electron energy following the decay of electronic states - Chiang, Ying-Chih; Otto, Frank; Meyer, Hans-Dieter; Cederbaum, Lorenz S. (Physical review letters, 2011)
In an electronic decay process followed by fragmentation the kinetic energy release and electron spectra can be measured. Classically they are the mirror image of each other, a fact which is often used in practice. Quantum expressions are derived for both spectra and analyzed. It is demonstrated that these spectra carry complementary quantum information and are related to the nuclear dynamics in different participating electronic states. Illustrative examples show that the classical picture of a mirror image can break down and shed light on the underlying physics.